Bukan Sekadar Kekuatan Normatif: Uni Eropa, Good Governance, dan Diskursus Pembangunan Indonesia Pasca-Orde Baru - Ahmad Rizky Mardhatillah Umar (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2014)
Indonesia and the European Union (EU) have been starting to cooperate in many sectors since 1990. However, there have been shifts the area of cooperation after the New Order. EU, through Partnership and Cooperation Agreement (firstly signed in 2003), has been agreed to take part in strengthening Indonesias civil society organisations. EU offers some funded program to be conducted by Indonesias civil society organisations in broad range of area, mainly in human rights, democratic participation, and development agenda, and good governance. This cooperation agreement made EU as one of main partner for Indonesias civil society organisations to strengthen their capacities in community empowerment and policy advocacy. However, EUs involvement in assisting civil society in post-Suharto Indonesia has also become an instrument for promoting EUs norms in Indonesia. This paper will raise two questions in relations to EUs involvement: (1) What is EUs main motive in assisting Indonesias development through civil society? (2) To what extent do the projects affect social and political practices in Indonesia? By using Foucaults concept of governmentality, this paper have analysed that EUs involvement in assisting civil society in Indonesia through its funded projects reflects EUs attempts to discipline the third world, particularly Indonesia and thus control the subjectivity through civil society engagement. This paper suggests that studies on EU power should address the changing discourse in international politics and how EU interacts with other global entity, particularly the third world, in a more critical perspective.Keywords: European Union, Civil Society, Development, Human Rights, Democracy, Normative Power Global Governmentality